2021
DOI: 10.3389/fmicb.2020.619878
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Colonizes and Disseminates to the Gastrointestinal Tract in the Presence of the Microbiota in a Severe Combined Immunodeficient Mouse Model

Abstract: Candida albicans is the leading cause of candidemia or other invasive candidiasis. Gastrointestinal colonization has been considered as the primary source of candidemia. However, few established mouse models that mimic this infection route are available. In the present study, we established a mouse model of disseminated candidiasis developed through the translocation of Candida from the gut. In this study, we developed a novel C. albicans GI colonization and dissemination animal model by using severe combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…In addition, obvious tissue damage, including epithelial hyperplasia and erosion accompanied by hyphal fungi, was found in the stomach of SC5314-infected mice, but neither hyperplasia nor tissue-associated fungi were observed in HLC54-infected mice ( Figure 1D ). Our data suggest that SC5314- but not HLC54-infected Rag2γc mice developed gastric candidiasis at 12 days post-infection, similar to our previous findings, which revealed that SC5314-infected Rag2γc mice exhibit signs of invasive infection, with 58% positive results in kidney/liver cultures within 2-3 weeks post-infection ( Pan et al., 2020 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, obvious tissue damage, including epithelial hyperplasia and erosion accompanied by hyphal fungi, was found in the stomach of SC5314-infected mice, but neither hyperplasia nor tissue-associated fungi were observed in HLC54-infected mice ( Figure 1D ). Our data suggest that SC5314- but not HLC54-infected Rag2γc mice developed gastric candidiasis at 12 days post-infection, similar to our previous findings, which revealed that SC5314-infected Rag2γc mice exhibit signs of invasive infection, with 58% positive results in kidney/liver cultures within 2-3 weeks post-infection ( Pan et al., 2020 ).…”
Section: Resultssupporting
confidence: 91%
“…To investigate the gut bacterial changes caused by C. albicans infection, we designed animal experiments according to previous reports ( Pan et al., 2020 ) and collected stool samples before infection and at 5 and 12 days post-infection (to represent the time of introduction and invasion, respectively) for bacterial 16S rRNA gene sequencing ( Figure 1A ). The colonization of C. albicans in the gut was confirmed by measuring the fungal counts in the feces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies and others also show that invading C. albicans hyphae produce substantial host damage that allows for material to pass through the barrier, potentially leading to translocation via mechanical lesions. 13 , 14 , 59 This degree of epithelial damage during translocation in vivo is likely given that there is an expansion of Candida spp. just prior to bloodstream infections along with a decrease in the total bacterial burden.…”
Section: Dissemination Via the Bloodstreammentioning
confidence: 99%
“…Several studies provide evidence that the human gastrointestinal (GI) tract serves as a source for systemic candidiasis [ 13 , 14 ••, 95 ]. This concept is supported by studies using mice, which demonstrate that C. albicans can translocate from the murine GI tract and establish systemic infection in severely immunocompromised animals [ 96 98 ]. In vitro interaction of C. albicans with enterocytes is similar to the interaction with other types of epithelial cells, with adhesion being followed by hypha formation, invasion, and damage driven by candidalysin [ 99 •].…”
Section: Colonization Of the Gut: A Source For Disseminated Infectionmentioning
confidence: 99%